2009
DOI: 10.1179/136217108x365296
|View full text |Cite
|
Sign up to set email alerts
|

Solution to problems of arc interruption and arc length control in tandem pulsed gas metal arc welding

Abstract: In the tandem pulsed gas metal arc welding, it is the most important issue to prevent adverse effects caused by electromagnetic interaction between the two adjacent arcs to prevent arc interruption. A pulse timing control can reduce arc interference in tandem pulsed gas metal arc welding. One effective way is to delay the pulse end timing of trailing arc by 0?4-0?5 ms from that of leading arc. In addition, arc length control is assured by pulse frequency modulation for the leading wire and pulse peak modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 8 publications
3
15
0
2
Order By: Relevance
“…In previous work, the influence of welding current on the resistance of GTAW arcs to extinction was studied to gain an understanding of the mechanisms involved in arc interruptions and to find ways of avoiding them [4]. The results showed that GTAW arcs are extinguished by external magnetic fields, but as the welding current is increased the arcs become more difficult to extinguish, which is in accordance to the results presented for tandem GMAW by Ueyama et al [5]. However, additional factors might influence the arc extinction phenomenon caused by another welding arc.…”
Section: Introductionsupporting
confidence: 81%
“…In previous work, the influence of welding current on the resistance of GTAW arcs to extinction was studied to gain an understanding of the mechanisms involved in arc interruptions and to find ways of avoiding them [4]. The results showed that GTAW arcs are extinguished by external magnetic fields, but as the welding current is increased the arcs become more difficult to extinguish, which is in accordance to the results presented for tandem GMAW by Ueyama et al [5]. However, additional factors might influence the arc extinction phenomenon caused by another welding arc.…”
Section: Introductionsupporting
confidence: 81%
“…An molten metal bulge was observed between the two wires in the weld pool. This kind of bulge was also observed by Kiran et al (2014) in tandem submerged arc welding and by Ueyama et al (2009) in tandem P-GMAW. From Fig.…”
Section: Weld Pool Behaviormentioning
confidence: 61%
“…As for the optimal phase matching for tandem P-GMAW, disagreement existed among researchers. Goecke (2001) and Ueyama et al (2009) reported that stable process can be ensured by applying a short pulse phase shift (0.4-0.5 ms). Lassaline et al (1989), Michie et al (1999), Savu (1999) and Yudodibroto et al (2006a) reported that optimal process stability was achieved when the two current pulses were in reverse phase, because the magnetic field of one arc was not strong enough to interfere with the other arc.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, Ueyama et al (2005) conducted an experiment with the leading current and trailing current having the same frequency and same phase (SFSP), and then they found that when the peak period of the trailing current was delayed by 0.5 ms more than that of the leading current, a steady welding process together with a satisfactory welding seam could be obtained. Moreover, by delaying the pulse end timing of the trailing arc by 0.4-0.5 ms from that of the leading arc, Ueyama et al (2009) work's effectively reduced the arc interference in tandem pulsed gas metal arc welding. Additionally, Motta et al (2007) showed that an inverse phase waveform is not a necessary condition for obtaining satisfactory welding seams.…”
Section: Introductionmentioning
confidence: 99%